Pengaruh Media Sosial terhadap Gaya Hidup Digital dan Pola Belajar Siswa SMA Negeri 1 Bagan Sinembah - Nur Ramaini; Rendra Widyatama (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the influence of social media use on digital lifestyles and its impact on students’ learning patterns at Bagan Sinembah State High School 1. A quantitative cross-sectional approach and the Uses and Gratification theoretical framework were applied in this study. Random sampling was used for data collection through the distribution of questionnaires to 92 respondents selected at random using the Slovin formula. Data analysis included testing for validity, reliability, normality, Pearson correlation, and linear regression using the SPSS data analysis program. The results of the study revealed the existence of a paradoxical dual effect. On one hand, there was a positive and significant influence of social media use on students’ digital lifestyles, with a correlation coefficient of 0.502 (Sig. 0.000). On the other hand, such digital interactions have a negative and significant impact on learning patterns with a correlation coefficient of -0.234 (Sig. 0.025), where high intensity of digital interactions was found to significantly reduce students’ concentration during learning. This Finding reveals that adolescents’ psychological needs often take precedence over their self-control. The implications of this study underscore the need for schools to shift from restrictive bans toward the implementation of comprehensive digital literacy programs within the curriculum.